Molecular testing stratifies the risk of structural recurrence in high risk differentiated thyroid cancer: a retrospective cohort study - Liu, Jie; Gao, Wensi; Zheng, Xiong; Wu, Shuping; Shi, Yi; Wang, Feng; Wu, Yu (Frontiers in Endocrinology, 2025)
BackgroundHigh-risk differentiated thyroid cancer in 2015 American Thyroid Association risk stratification system (ATA-RSS) exhibits a significantly increased probability of recurrence and poor outcomes. This study aimed to investigate the molecular profiles of high-risk differentiated thyroid cancer and to assess the role of molecular testing in enhancing prognostic risk stratification.MethodsIn a single-center study conducted at Fujian Cancer Hospital, Fujian Province, China, a consecutive cohort of differentiated thyroid cancer patients identified as high-risk under 2015 ATA-RSS criteria were retrospectively assessed, spanning from November 1, 2019, to March 31, 2022. Molecular characterize groups were conducted using an 18-gene next-generation sequencing assay. Patients harboring mutations in the TERT promoter, TP53, or PIK3CA genes were categorized as the high molecular risk group, while all others were assigned to the non-high molecular risk group.ResultsAmong the 108 cases, 32 (29.6%) fell into the high molecular risk group, characterized by a significantly older mean age (57.8 vs. 42.6 years, p < 0.001), larger tumor size (3.1 cm vs. 2.0 cm, p = 0.003), a higher incidence of aggressive pathological subtypes (43.8% vs. 7.9%, p < 0.001), and an increased occurrence of distant metastasis (34.4% vs. 7.9%, p = 0.001). Over a median follow-up period of 32.5 months, this high-risk group demonstrated an elevated risk of local recurrence (32.1% vs. 9.5%, HR: 3.18, 95% CI: 1.15-8.78) and metachronous distant metastasis (38.1% vs. 2.9%, HR: 12.54, 95% CI: 2.60-60.41). Multivariate COX regression analysis confirmed that molecular characterize groups (HR: 5.77, 95% CI: 2.18-15.23, p < 0.001) and tumor size (HR: 1.32, 95% CI: 1.00-1.74, p = 0.047) independently predicted recurrence-free survival.ConclusionATA-RSS high-risk differentiated thyroid cancer often presents with late-hit genetic alterations, which are strongly associated with increased likelihood of structural recurrence. Molecular testing offers a precise approach to recurrence risk stratification in high-risk cases, enabling personalized follow-up and treatment strategies tailored to the specific prognostic profile.